A business model for dynamic composition of telecommunication web services. - Karunamurthy, Rajesh; Khendek, Ferhat; Glitho, Roch H.
Web service composition is a mechanism for creating new web services from existing Web services. Web service composition enables rapid service creation by reusing existing services. Dynamic composition is composition at runtime. A business model defines the different parties involved in service provisioning and their relationships. However, the existing business models are not suitable for Web service composition. This article proposes a novel business model for dynamic web service composition that is an extension of the standard web service business model. The proposed model is demand-driven, where services can be dynamically composed based on the demand for them. We introduce new business roles and new interactions. We have provided a UDDI-based implementation of our new model by proposing extensions to the subscription API of UDDI. We have developed a proof-of-concept prototype, and have made some preliminary performance measurements. The performance analysis shows that the UDDI extensions incur acceptable performance penalization.
Keywords: Web service composition; Performance penalization; Proof-of-concept prototype; Rapid service creation; Service provisioning; Telecommunication web services